The impacts of altitude and seed pretreatments on seedling emergence of Syrian juniper (Juniperus drupacea (Labill.) Ant. et Kotschy) - Yucedag, Cengiz; Cetin, Mehmet; Ozel, Halil Baris; Abo Aisha, Adel Easa Saad; Alrabiti, Osama B. Muragaa; AL.JAMA, Akram Mohamed Omar (Springer Science and Business Media LLC, 2021)
Abstract Background Syrian juniper is an economically important species and in danger of extinction. For these reasons, the best seedling production methods of the species should be determined and its plantations should be established. The aim of the study is to examine the impacts of altitude and different pretreatment combinations of cold and warm stratifications, citric acid, shaking seeds in bottles with crushed glass, and different stimulating agents including Baikal EM1, Biohumus, Polystimulin A6 and K hormones (PS-A6 and PS-K) on seed germination of Syrian juniper. To conduct the study, the cones of the Syrian junipers were collected from three different altitudes (1000, 1200, and 1400 m a.s.l.) within the boundaries of Forest Management Directorate of Bozyazı, Mersin in Turkey. The seeds were subjected to three replicates per one treatment (altitude in interaction with pretreatment). There were 100 seeds per replicate. Results Two-way ANOVA revealed significant effects of altitude, pretreatment, and their interaction on seedling emergence of Syrian juniper. Seeds from higher altitudes had higher germination rates in all pretreatments. The highest percent emergence (85%) was recorded in the combination consisting of shaking with crushed glass, both cold and warm stratification, and successive application of stimulators PS-A6 and PS-K. All the treatments with most germinating seeds encompassed shaking in crushed glass or soaking in citric acid, both warm and cold stratifications, and application of stimulating agents. Conclusions The use of seeds from higher altitudes should be considered for seedling production of Syrian juniper due to their higher germination potential. Beyond altitudinal differences, specific pretreatments can rise germination potential more than twofold.
Keywords: Citric acid; Ecology; Ecological Modeling; Auxin; Germination; Stratification; Cytokine; Citric Acid; QH540-549.5; 15. Life on land